Developmental entrepreneurship adversity, risk, and isolation - Galbraith, Craig; Stiles, Curt H. (Elsevier JAI, 2006)
This series is an outlet for unique, often cutting edge, business research with an international flavour. Articles that appear in each volume are original, peer-reviewed manuscripts, selected to support both the volume's theme and to provide a cross-section of high-quality knowledge concerning the selected topic.
Keywords: Entrepreneurship.; Economic development.; elektronické knihy; electronic books